Light utility vehicle data in Latvia: methodology, key findings, and applications - Zemīte, Dita; Niedra, Aiva; Savrasovs, Mihails; Spiridovska, Nadežda; Budiloviča, Evelīna (Transport, 2026)
The number of Light Utility Vehicles (LUVs) in the national vehicle registers keeps increasing, especially in the context of the COVID-19 pandemic. This trend is mainly due to the accelerated growth of e-commerce and home delivery services, as well as the shift in delivery methods from traditional courier and postal services to the use of parcel lockers. Although LUV accounts for a relatively small share of total freight tonnage compared to other freight modes, it accounts for a disproportionately large share of Vehicle-Kilometres (vkm) travelled, particularly in densely populated urban areas. This contributes to increased transport-related emissions and poses significant challenges for urban transport systems, including increased infrastructure pressure, traffic congestion and complexity in traffic management, particularly in relation to the planning of low or zero-emission zones in cities. In the EU, official freight transport statistics may not include vehicles with a maximum permissible load of up to 3500 kg, meaning that such vehicles are not systematically collected. Therefore, the development of appropriate methodologies and the analysis of available data on LUV are both necessary and valuable, especially given their increasing prevalence. These efforts can provide essential insights to support evidence-based transport planning and policymaking. The importance of detailed freight transport statistics is underlined by major EU policy initiatives such as the White Paper (EC 2011), the European Green Deal (EC 2019) and the Sustainable and Smart Mobility Strategy (EC 2020) aimed at reducing GreenHouse Gas (GHG) emissions from the transport sector. The goal of this research is to propose a methodology for LUV data collection, share data insights from its initial approval by presenting key findings, and suggest further uses of the data. First published online 16 June 2026